On Waiting-time Estimation for Outpatients at Department of Ophthalmology - Kamiura, Naotake; Saitoh, Ayumu; Isokawa, Teijiro; Matsui, Nobuyuki; Tabuchi, Hitoshi (2012 Fifth International Conference on Emerging Trends in Engineering and Technology, 2012)
In this paper, waiting-time estimation is presented for outpatients visiting department of ophthalmology. It determines the number of virtual outpatients according to the probability density functions of the gamma distribution. Assignments of arrival time intervals for such outpatients depend on random numbers generated from the exponential distribution. It assumes that outpatients undergo all examinations within the waiting time. The examination order is determined by six rules established by the surveys at the hospital. Once a target outpatient specifies a day of the week and arrival time of the outpatient desiring, disease name, and name of ophthalmologist at the time of making an appointment, the proposed system calculates the waiting time for the outpatient. Experimental results establish that the difference between estimated waiting time and actual waiting time is acceptable to outpatients.